Transcriptome Analysis of Floral Buds Deciphered an Irregular Course of Meiosis in Polyploid Brassica rapa - Braynen, Janeen; Yang, Yan; Wei, Fang; Cao, Gangqiang; Shi, Gongyao; Tian, Baoming; Zhang, Xiaowei; Jia, Hao; Wei, Xiaochun; Wei, Zhenzhen (Frontiers in Plant Science, 2017)
Polyploidy is a fundamental process in plant evolution. Understanding the polyploidy-associated effects on plant reproduction is essential for polyploid breeding program. In the present study, our cytological analysis firstly demonstrated that an overall course of meiosis was apparently distorted in the synthetic polyploid B.rapa in comparison with its diploid progenitor. To elucidate genetic basis of this irregular meiosis at a molecular level, the comparative RNA-seq analysis was further used to investigate differential genetic regulation of developing floral buds identified at meiosis between autotetraploid and diploid B.rapa. In total, compared to its diploid counterparts, among all 40,927 expressed genes revealed, 4601 differentially expressed genes (DEGs) were identified in the floral buds of autotetraploid B.rapa, among which 288 DEGs annotated were involved in meiosis. Notably, DMC1 identified as previously known meiosis-specific genes involved in inter-homologous chromosome dependent repair of DNA double stranded breaks (DSBs)DNA repair and meiotic recombination, was significantly down-regulated in autotetraploid B.rapa, which presumably contributed to alternation abnormal progression during in the meiosis I course. Although certain DEGs associated with RNA helicase, cell cycling and somatic DNA repair were upwere up-regulated after genome duplication, genes associated with meiotic DSB repair was significantly down-regulated.. In addition, Tthe KEGG pathway analysis also revealed that two putative meiosis genes involved in that homologous recombination were down-regulated in, spliceosome assembly, and base excision were altered in autotetraploid B.rapa in comparison with diploids. Furthermore, the expression of randomly selected DEGs by RNA-seq analysis was confirmed by quantitative real-time PCR analysis in both B.rapa and A.thaliana. Our results firstly account for adverse effects of polyploidy on an entire course of meiosis at both cytological and transcriptomic levels, and allow for a comprehensive understanding of the uniformity and differences in the transcriptome of floral buds at meiosis between diploid and polyploid B.rapa as well.